Scoring the Positive Margin Status in Partial Nephrectomy - Al Sheikh , M; Aslam, Z; Curry , D; Wahaily, A; O, Abed Al-Mula; Thwaini , A (Jordan Medical Journal, 2022)
Objective A clear resection margin is one of the trifecta outcomes in partial nephrectomy. We proposed a positive surgical margin scoring system and implemented it in our cases to assess its effect on the oncological outcomes. Methods Retrospective review of prospectively collected multi-center data was performed for all the partial nephrectomy (PN) procedures performed between April 2009 and August 2019. Demographic data, RENAL nephrometry score, peri-operative data and margin status were collected. Positive surgical margin (PSM) cases were given a scoring system of I, II and III for PSM that are <3mms, 3-5mms and >5 mms, respectively. Postoperative, oncological results and adverse events were using Stats Direct. Data analysis was performed using t-test. Comparative data between the two groups was calculated using z-score calculator. p values of 0.05 or less were considered statistically significant. Results A total of 339 PN procedures were performed for histologically proven renal cancer. Forty four patients had PSM. There were 17, 16 and 11 patients with score I, II and III PSM, respectively. Those with a high RENAL nephrometry score had the highest rate of PSM (n=21) as opposed to the intermediate (n=13) and the low (n=10) score groups. After an average follow up of 38 months (10- 132), a total of 21 recurrences were recorded; 14 had clear resection margins, 7 were PSM (PSM-I=1. PSM-II=2, PSM-III=4, respectively). Conclusion Overall patients with PSM status have a low chance of recurrent or metastatic disease although those with a wider PSM (III) have a higher chance of recurrent and/or metastatic disease. Tumour grade and pathological T-stage are independent factors for recurrence/metastasis. Larger cohort and longer follow up would be recommended.